Analysis on the Trends and Characteristics of Automobile Recalls in China. Issue 1 (October 2020) - Feng, Yongqin; Li, Wenzhao; Zhang, Xiaorui; Liu, Le
Abstract: Based on the statistical data provided by the State Administration for Market Regulation, China Automobile Industry Association and China Consumers' Association, this study analyzes the trends and characteristics of automobile recalls in China from 2008 to 2017. Studies have shown that automobile recalls in China have become a normal trend, there is a recall almost every two days and most recalls are initiated by a few automobile manufacturers. The recall of auto brands such as Volkswagen and Honda usually occur in the first 5 years of the model year. This shows that consumers should pay more attention to the after-sales and maintenance services in this period when buying a car.